Introduction to modes and their designation in circular and elliptical fibers - Kumar, Deepak; Choudhury, Pankaj Kumar (American Association of Physics Teachers, 2007)
Some basic ideas are presented to clarify the concept of modes in optical fibers. We describe the formation of modes and the indexing schemes in circular and elliptical core fibers.